Effects of pearling on proximate composition, dough rheology, bread-making quality and health-promoting components of elite wheat cultivars - Wenfei Tian; Lei Zhi; Tiantian Chen; Xue Gong; Yan Zhang; Zhonghu He (Elsevier, 2024)
Though the health benefits of whole wheat products have been widely recognized, their less desirable processing qualities limited consumers’ acceptance. Thus, it is imperative to develop processing techniques for balanced nutritional and processing qualities. In this study, we investigated impacts of two grain pearling (debranning) levels on proximate composition, dough rheological properties, food-making quality, arabinoxylans (AXs), alkylresorcinols (ARs) and phenolic acids composition of two elite bread wheat cultivars. Pearled flour (PF) of Zhongmai 175 retained very good dough extensibility (190.7–195.5 mm), while PF of Zhongmai 578 retained medium-to-strong gluten strength and acceptable bread-making quality. Compared to whole wheat flour, PF preserved major portion of the health-promoting components in wheat grains, i.e., 71.4–94.0 % for water-extractable AXs, 68.1–86.3 % for total AXs, 71.4–92.7 % for alkylresorcinols, 85.5–98.9 % for soluble ferulic acid and 67.3–83.3 % for insoluble-bound ferulic acid. Further investigation is needed to understand the effects of different kernel sizes and debranning rates on nutritional profiles of pearled grains. Taken together, our results suggested that grain pearling can be used to produce wheat products with balanced nutritional and processing quality for improved human health.